2015
DOI: 10.5367/te.2014.0442
|View full text |Cite
|
Sign up to set email alerts
|

Tourism and Poverty Reduction: An Economic Sector Analysis for Costa Rica and Nicaragua

Abstract: This study examines the existence of a long-run relationship between indigence or extreme poverty reduction and agricultural, manufacturing and tourism development in Costa Rica and Nicaragua. An econometric methodology consisting of an autoregressive distributed lag bounds testing approach to co-integration is used. For Costa Rica, agricultural and manufacturing (not statistically significant) and tourism development are negatively related to indigence poverty with estimated elasticity values of −0.50 for agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 62 publications
4
46
0
2
Order By: Relevance
“…Tourism development indicates a significant relationship with agriculture; to the best of our knowledge, the literature is silent on the econometric relationship between tourism and agriculture. The findings further suggest that tourism has a significant negative relationship with poverty, therefore our results are similar to those of Vanegas Sr, Gartner [36] in Costa Rica and Nicaragua.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Tourism development indicates a significant relationship with agriculture; to the best of our knowledge, the literature is silent on the econometric relationship between tourism and agriculture. The findings further suggest that tourism has a significant negative relationship with poverty, therefore our results are similar to those of Vanegas Sr, Gartner [36] in Costa Rica and Nicaragua.…”
Section: Resultssupporting
confidence: 87%
“…The literature on the empirical investigation between tourism and agriculture development is quite silent. In a multivariate analysis using ARDL and the Granger causality mechanism, Vanegas Sr, Gartner [36] suggested a unidirectional causality running from tourism development to agriculture development in Costa Rica and Nicaragua, proposing that tourism leads to agriculture development. Scholars have suggested that tourism increases the demand for local food products, which provides support for agriculture development, hence increases the economic multiplier effects [37].…”
Section: Tourism and Agriculture Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the contribution of the tourism sector to both the world GDP and the provision of employment is increasingly high (Eugenio-Martin et al, 2008). In addition, the tourism sectors have also contributed to reduce the amount of poverty as it did in Costa Rica and Nicaragua (Vanegas et al, 2015). Further, on a more micro scale, tourism has contributed to engage the indigenous peoples in the search for development options (Capucci, 2016).…”
Section: Introductionmentioning
confidence: 99%